2016
DOI: 10.2134/jeq2015.10.0536
|View full text |Cite
|
Sign up to set email alerts
|

Using the Provenance of Sediment and Bioavailable Phosphorus to Help Mitigate Water Quality Impact in an Agricultural Catchment

Abstract: The quality and health of surface waters can be impaired by sediment and sediment-bound phosphorus (P). The Waituna Lagoon catchment in southern New Zealand has undergone agricultural intensification that has been linked to increases in sediment and sediment-bound bioavailable P (BAP) in the lagoon. Time-integrated samplers trapped suspended sediment from the water column, and their geochemical signature was compared with likely sources (stream banks, stream beds, topsoil, and subsoil) in each of the lagoon's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…These strategies may also be beneficial and act as insurance against the failure of fencing to mitigate contaminant losses. For example, much anecdotal evidence highlights erosion of stream banks and SS loss where fencing is only temporary (McDowell et al, 2016b). Furthermore, contaminant losses can be exacerbated where significant deposition of excreta is associated with stock traffic (e.g., fenceline pacing by red deer) and ephemeral channels carry excreta to the stream (McDowell, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These strategies may also be beneficial and act as insurance against the failure of fencing to mitigate contaminant losses. For example, much anecdotal evidence highlights erosion of stream banks and SS loss where fencing is only temporary (McDowell et al, 2016b). Furthermore, contaminant losses can be exacerbated where significant deposition of excreta is associated with stock traffic (e.g., fenceline pacing by red deer) and ephemeral channels carry excreta to the stream (McDowell, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The transport of both PP and dissolved P in rivers is complex and can be affected by numerous variables. Phosphorus can originate from various sources in a watershed (Grundtner et al, 2014; McDowell et al, 2016), and numerous studies have shown that P can transform between dissolved and particulate along the course of a river (Reddy et al, 1999; Withers and Jarvie, 2008). Furthermore, P may also be affected by legacies of land use management, which can affect retention and remobilization of P along the continuum from soils to rivers to lakes (Sharpley et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Soil erodibility is linked to aggregate stability that is considered an important indicator of soil physical quality. As the fine soil particles are susceptible to loss by erosion, bioavailable P attached to such particles is believed to have a negative impact on water quality (McDowell et al ., ; Salm et al ., ). The distribution and bioavailability of soil P associated with different aggregate size classes are strongly controlled by the form of P applied and soil texture (Geisseler et al ., ; Ahmed et al ., ).…”
Section: Introductionmentioning
confidence: 97%